Hyperfine characterization of metastable tetragonal configurations in Pr doped zirconias - Caracoche, Maria Cristina (2004)
The PrxZr1-xO2 ceramic system obtained by coprecipitation has been investigated atzirconium sites as a function of Pr content (1, 10, and 15 mol %) and of annealing temperatureby means of the perturbed angular correlations (PAC) technique. Praseodimium enterszirconia forming a tetragonal solid solution whose extent increases with Pr content. In 10and 15 mol % Pr-doped samples, metastable tetragonal zirconia is present in its two knownt- and t¢-forms, the latter form being the one which involves a higher dopant concentration.While Rietveld refinement and thermal analyses indicate the uncompleted crystallizationof the as-obtained powders, PAC allows the phase identification of the amorphous residues.Minor changes observed in the hyperfine interaction at high temperatures reveal the incipientceramic degradation. Experiments indicate that, up to 15 mol % of dopant content, Pr behavesas an efficient zirconia stabilizer.